Developing an Instruction Model for News Writing Based on the Cooperative Type Group Investigation Strategy - Wismanto, Agus; Suyoto, Suyoto; Ulumuddin, Arisul (JOLLT Journal of Languages and Language Teaching, 2022)
This study aims to produce a learning model of news writing skills using the cooperative type group investigation strategy. This study was a research and development (R&D) that followed Borg & Gall's development procedure. The subject of study was students and lecturers at the University of PGRI Semarang. The developed learning model includes the components of introduction, concepts, advantages, objectives, characteristics, and steps in the learning of news writing based on the cooperative type group investigation strategy. The expert, user/practitioner, expert, user/practitioner, and field testing results showed that the developed learning model could improve the students’ news writing skills in terms of the process and the product. The success in the process was indicated by their activeness and seriousness in the steps of news writing activities based on the cooperative type group investigation strategy. The success in the product was indicated by the improvement of their news writing quality in the aspects of contents/substances and mechanics (spelling and punctuation). The ability to write news to PBSI students with learning models based on cooperative type group investigation strategy is better than students who study with conventional learning models.